Exposed – a semantic concept analysis of its origin, meaning change over time and its relevance for caring science - Sofia Almerud Österberg; Ulrica Hörberg; Lise-Lotte Ozolins; Carina Werkander Harstäde; Carina Elmqvist (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose A patient is vulnerable and exposed due to illness, relies on and surrender to other people. In caring this means a special dependency. The aim of this study was to describe the origin of the concept ‘exposed’, to elucidate how the definition of this term has changed over time, and to outline its relevance in caring science. Method A semantic concept analysis in two phases was conducted. Results The findings show that over time, the degree of binding of the following synonyms has become stronger; unprotected/defenseless, naked/bare, pressed/jostled and unsafe/unprotected and can easily be transferred to a clinical nursing context. Conclusions This study provides a deeper understanding of the concept 'exposed' semantically. Being exposed is a profound experience for patients who need to be seen as the person they really are. A life-world led care has an existential power that can support professionals, strengthen patients’ health processes, and alleviate the patient’s suffering.